2022
DOI: 10.1186/s13063-022-06598-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of synbiotic and/or vitamin D supplementation on gut-muscle axis in overweight and obese women: a study protocol for a double-blind, randomized, placebo-controlled trial

Abstract: Background Sarcopenia refers to an age-related loss of skeletal muscle content, strength, and function, leading to a decrease in mobility. Obesity may exacerbate age-related complications such as sarcopenia through inflammatory pathways. In addition, intestinal dysbiosis has been proposed as an emerging contributor to sarcopenia due to the stimulation of the immune system and elevated barrier permeability of the intestine. Targeting microbiome with synbiotic and vitamin D supplementation may mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Besides directly affecting calcium absorption, vitamin D also regulates intestinal mucosal homeostasis by maintaining the integrity of the intestinal barrier, which affects immune system function and inflammatory responses. 216 , 217 Vitamin D improves homeostasis of the intestinal microbiome and facilitates muscle anabolism 218 . Vitamin D can inhibit the levels of pro-inflammatory factors and promote the anti-inflammatory factors secretion of body.…”
Section: Effective Intervention Of Musculoskeletal Health Based On In...mentioning
confidence: 99%
“…Besides directly affecting calcium absorption, vitamin D also regulates intestinal mucosal homeostasis by maintaining the integrity of the intestinal barrier, which affects immune system function and inflammatory responses. 216 , 217 Vitamin D improves homeostasis of the intestinal microbiome and facilitates muscle anabolism 218 . Vitamin D can inhibit the levels of pro-inflammatory factors and promote the anti-inflammatory factors secretion of body.…”
Section: Effective Intervention Of Musculoskeletal Health Based On In...mentioning
confidence: 99%
“…The induced exercise stress reduced the level of Turicibacter and increased the number of Ruminococcus gnavus , which plays a significant role in immune function [ 63 ]. In addition, various studies indicated that probiotics can support healthy digestion and resistance function, as well as aid in the regulation of muscle anabolism, the elevation of insulin sensitivity, the increase in amino acid biosynthesis or AMPK signaling, and the limiting of low-grade inflammation and oxidative stress by metabolite production [ 23 , 27 , 125 ]. The increased relative abundance of Proteobacteria is considered as a potential diagnostic criterion for the risk of metabolic disorders and fatigue diseases [ 126 ].…”
Section: Polysaccharides Ameliorate Fatigue Via the Gut-muscle Axismentioning
confidence: 99%
“…Over the past few decades, the functions and properties of skeletal muscle have been extensively studied, which contributes to the characterization of muscle and provides unique insights for the inter-tissue communication network of the organism [ 24 , 49 ]. Numerous factors contribute to the loss of muscle mass and function, such as senility [ 26 ], special diet [ 27 ], exercise [ 46 ], inflammation [ 32 ], mitochondrial dysfunction [ 16 ], etc. Another important factor not to be neglected is the gut physiology, as the gut microbiota can interact with skeletal muscle by regulating various processes affecting host physiology, including those involving systemic inflammation, energy provision and use, oxidative stress, and mitochondrial function, as well as endocrine and insulin resistance [ 23 , 130 ].…”
Section: Polysaccharides Ameliorate Fatigue Via the Gut-muscle Axismentioning
confidence: 99%
See 2 more Smart Citations